2002
DOI: 10.1086/338445
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy with Protease Inhibitors Has an Early, Immune Reconstitution–Independent Beneficial Effect onCandidaVirulence and Oral Candidiasis in Human Immunodeficiency Virus–Infected Subjects

Abstract: Highly active antiretroviral therapies (HAARTs) that contain human immunodeficiency virus (HIV) protease inhibitors (PIs) or nonnucleoside reverse-transcriptase inhibitors (NNRTIs) were compared for their effect on secretory aspartyl proteinase (Sap), a virulence trait for mucosal candidiasis. In therapy-naive HIV-positive subjects, oral Sap was detected in 11, 6, 3, 0, and 0 of 15 subjects treated with PI-HAART and in 7, 7, 9, 6, and 5 of 15 subjects treated with NNRTI-HAART, on days 0, 14, 30, 90, and 180 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
3
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 31 publications
4
73
3
3
Order By: Relevance
“…Moreover, the time patients were free of oral candidiasis increased with the addition of new drugs to the antiretroviral regimen. These results are in agreement with findings reported in previous studies, which defend the hypothesis that antiretroviral drugs not only reestablish systemic immunological competence, but also improve the immune response of the oral mucosa against the fungus 44,45 . This may explain situations in which the resolution of oral candidiasis precedes the reestablishment of normal CD4+ T lymphocyte counts 46 .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the time patients were free of oral candidiasis increased with the addition of new drugs to the antiretroviral regimen. These results are in agreement with findings reported in previous studies, which defend the hypothesis that antiretroviral drugs not only reestablish systemic immunological competence, but also improve the immune response of the oral mucosa against the fungus 44,45 . This may explain situations in which the resolution of oral candidiasis precedes the reestablishment of normal CD4+ T lymphocyte counts 46 .…”
Section: Discussionsupporting
confidence: 93%
“…albicans SAP1-3 and SAP4-6 gene families are not pseudogenes that have subsisted to purifying selection and concerted evolution, but apparently have acquired new and specific functions in nitrogen metabolism, switching, and cell adherence (Cassone et al 2002, Felk et al 2002, Ripeau et al 2002, Schofield et al 2003. C. tropicalis has only one gene (SAPT4) related to the C. albicans SAP1-3 and SAP4-6 families.…”
Section: Discussionmentioning
confidence: 99%
“…Such a thing related an improving immunity thereby reduces the potential risk of opportunistic infections such as Candida species. 3,6,9,14 In addition, combination therapies has been significantly associated with increases in neutrophils count. Neutrophils plays a pivotal role in the defense mechanisms against Candida.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,12 The presence of oral candidiasis in HIV-infected and AIDS patients was associated with a number factors including low CD4 counts, increased viral load, xerostomia, age and Secretory aspartyl proteinase (Sap), extracellular hydrolytic enzyme was product by Candida. 7,10,13,14 Oral candidiasis occurs more frequently in HIVinfected patients with low CD4 counts. Imam et al found a statistically significant increase in the frequency of HIVrelated oral candidiaisis in patients with CD4 counts of less than 300 cells/mm 3 .…”
Section: Hiv/aids and Oral Candidiasismentioning
confidence: 99%